2020
DOI: 10.1021/acs.langmuir.0c02945
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Transparent and Microstructured Superhydrophobic Substrates Using Additive Manufacturing

Abstract: We report facile one- and two-step processes for the fabrication of transparent ultrahydrophobic surfaces and three-dimensional (3D)-printed superhydrophobic (SH) microstructures, respectively. In the one-step method, polydimethylsiloxane (PDMS) solution is treated thermally at 350 °C for 4 h, while PDMS-soot is generated and deposited on a glass slide to obtain a transparent SH surface without further chemical modification. For the two-step approach, SH surfaces are obtained by incorporating a 3D printing tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…In order to further explore the chemical heterogeneity and robustness of the prepared surface, the dynamic contact angles were evaluated by an extension/contraction method. [45][46][47] The results showed that the advancing and receding contact angles were 155.6°and 150.8°, respectively, with a hysteresis of 4.8°, which indicate that the surface has good hydrophobic uniformity.…”
Section: Resultsmentioning
confidence: 97%
“…In order to further explore the chemical heterogeneity and robustness of the prepared surface, the dynamic contact angles were evaluated by an extension/contraction method. [45][46][47] The results showed that the advancing and receding contact angles were 155.6°and 150.8°, respectively, with a hysteresis of 4.8°, which indicate that the surface has good hydrophobic uniformity.…”
Section: Resultsmentioning
confidence: 97%
“…Measurement of advancing contact angle ( θ A ), receding contact angle ( θ R ) and contact angle hysteresis were according to literatures 31–33 . Specifically, a 5 μL water droplet was first placed on the sample to achieve a stable equilibrium state.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of advancing contact angle (θ A ), receding contact angle (θ R ) and contact angle hysteresis were according to literatures. [31][32][33] Specifically, a 5 μL water droplet was first placed on the sample to achieve a stable equilibrium state. Then 3 μL water was injected in which an increase in the volume and subsequently in the base diameter of the droplet was observed.…”
Section: Characterizationmentioning
confidence: 99%
“…To theoretically predict the stable wetting states for water and ionic liquids on the studied surface, we used a model based on the comparison between the surface energies for a CB and a Wenzel drop on hydrophobic microstructures. The total surface energy for a CB or a Wenzel drop on the hydrophobic microtextures, denoted by E CB and E W , respectively, can be expressed by ,,, .25ex2ex E CB = S normalb false[ γ SG r + γ LG ( 1 ϕ false( 1 + 0.25em cos nobreak0em.25em⁡ θ normalY false) false) ] + γ LG S cap E normalW = S normalb [ γ SG r γ LG r cos θ Y ] + γ LG S cap where S b is the drop’s base surface area, γ SG and γ LG are the solid–gas and liquid–gas interfacial tensions, respectively, r is the surface roughness, ϕ is the packing fraction, and S cap is the spherical cap surface area of the water drop completely in contact with the surrounding air.…”
Section: Theoreticalmentioning
confidence: 99%
“…The difference between the CB and Wenzel energies, Δ E = E CB – E W , enables us to predict the critical contact angle θ* when equating the two energies E CB = E W . Using the above equations, one can arrive at the physical criterion of the critical contact angle θ* that delineates the surface parameters for a stable CB vs Wenzel state, by equating E CB = E W ,,, 0.25em cos nobreak0em.25em⁡ θ * = ϕ 1 r ϕ This model suggests that a CB droplet is thermodynamically more stable when E CB < E W , which corresponds to a larger contact angle, θ > θ*. In addition, a stable Wenzel occurs when E W has lower energy compared to that of a CB wetting mode, that is, E W < E CB , by tuning the surface parameters of r and ϕ .…”
Section: Theoreticalmentioning
confidence: 99%